Supplementing white maize masa with anthocyanins: Effects on masa rheology and on the in vitro digestibility and hardness of tortillas. (January 2020) - Vernon-Carter, E.J.; Alvarez-Ramirez, J.; Bello-Perez, L.A.; Gonzalez, M.; Reyes, I.; Alvarez-Poblano, L.
Abstract: The aim of this work was to supplement masa made from nixtamalized white maize flour (NWMF) with anthocyanins (0.0, 0.03, 0.06 and 0.12 g/100 g of masa), and to evaluate the effects on the rheological properties of the masa and on color, staling, in vitro digestibility, and hardness of tortillas. Tortilla baking reduced the content of anthocyanins by about 10%. The color parameters of the tortillas added with anthocyanins was similar to that of tortillas made with blue maize. Attenuated total reflection ATR-FTIR spectra showed that the 1022/1047 peak ratio increased, indicative that retrogradation increased with storage time, but the ratio was significantly lower for tortillas with added anthocyanins than without them, and lower for higher anthocyanins concentration. Freshly made tortillas added with anthocyanins exhibited lower ready digestible (about 35%) and slowly digestible (about 20%), but higher resistant (about 45%) starch fractions. Tortillas with 0.12 g of anthocyanins showed significantly lower hardness than the control tortillas (without added anthocyanins). Both previous mentioned effects can be associated with retrogradation, which on turn could be linked to anthocyanins-starch complexes and inhibition of amylolytic enzymes. Graphical abstract: Image 1 Highlights: Anthocyanins reduced hardness of white maize tortillas. Cooking degraded only a small fraction of added anthocyanins. Anthocyanins promoted the formation of slowly digestible starch.